Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics: Main Volume 2021
DOI: 10.18653/v1/2021.eacl-main.171
|View full text |Cite
|
Sign up to set email alerts
|

“Laughing at you or with you”: The Role of Sarcasm in Shaping the Disagreement Space

Abstract: Detecting arguments in online interactions is useful to understand how conflicts arise and get resolved. Users often use figurative language, such as sarcasm, either as persuasive devices or to attack the opponent by an ad hominem argument. To further our understanding of the role of sarcasm in shaping the disagreement space, we present a thorough experimental setup using a corpus annotated with both argumentative moves (agree/disagree) and sarcasm. We exploit joint modeling in terms of (a) applying discrete f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Existing work on agreement analysis is aimed at (1) identifying language that indicates disagreement (e.g., Niculae and Danescu-Niculescu-Mizil, 2016;Wojatzki et al, 2018;Fischer et al, 2022), (2) leveraging stylistic choices like sarcasm for detecting disagreement (Ghosh et al, 2021), (3) finding stance and target pairs, followed by the traditional stance classification (e.g., Chen et al, 2019;De Kock and Vlachos, 2021), and (4) mixing de-tailed opinion information using e.g., logic of evaluation (Draws et al, 2022). Recently, adding social role context to textual comments was shown to have a positive impact on the agreement analysis task (Luo et al, 2023), which indicates the usefulness of background information.…”
Section: (Dis)-agreement and Discussion Analysismentioning
confidence: 99%
“…Existing work on agreement analysis is aimed at (1) identifying language that indicates disagreement (e.g., Niculae and Danescu-Niculescu-Mizil, 2016;Wojatzki et al, 2018;Fischer et al, 2022), (2) leveraging stylistic choices like sarcasm for detecting disagreement (Ghosh et al, 2021), (3) finding stance and target pairs, followed by the traditional stance classification (e.g., Chen et al, 2019;De Kock and Vlachos, 2021), and (4) mixing de-tailed opinion information using e.g., logic of evaluation (Draws et al, 2022). Recently, adding social role context to textual comments was shown to have a positive impact on the agreement analysis task (Luo et al, 2023), which indicates the usefulness of background information.…”
Section: (Dis)-agreement and Discussion Analysismentioning
confidence: 99%
“…The pre-trained Bidirectional Encoder Representations from Transformer (BERT) (Devlin et al, 2019) model has shown to be effective in various NLP models including sentence classification and sentence-pair classification. BERT has also produced excellent results in various argument mining tasks (Chakrabarty et al, 2019;Reimers et al, 2019;Ghosh et al, 2021). In this work, we leverage the standard pre-trained BERT model (bert-baseduncased) (Devlin et al, 2019) to create the model for our revision classification task.…”
Section: Added Undesirable Reasoningmentioning
confidence: 99%
“…Accurate and automated identification of verbal irony may allow users' genuine intentions to be understood, thereby facilitating numerous tasks in natural language processing, including e.g. sentiment analysis [6], hate speech detection [7], and argument detection [8].…”
Section: Introductionmentioning
confidence: 99%